Has the cancer-related death trend been changing in Turkey? An evaluation of the period between 2009 and 2019 - AY, NADİYE PINAR; TEKER SAYIN, AYŞE GÜLSEN (My University, 2022)
Background: The objective of this study was to determine the trend of cancer-related death rates between 2009 and 2019 in Turkey for all cancers combined and the five cancer types with the highest mortality: lung, stomach, pancreas, breast, and colon cancers. Methods: Cancer mortality data were obtained from the Turkish Statistical Institute (TURKSTAT) and standardized by age using the World Health Organization (WHO) standard population ratios. The change in cancerrelated mortality over the years was evaluated using Joinpoint Regression Analysis (JRA). Results: Total cancer-related deaths increased by 2.2% annually between 2009 and 2014 and decreased by 2.9% annually between 2014 and 2019 (p < 0.05). Among men; lung cancer-related deaths increased by 2.4% annually between 2009 and 2014 and decreased by 3.4% annually between 2014 and 2019 (p < 0.05), stomach cancer-related deaths decreased by 5.1% annually between 2014 and 2019 (p < 0.05), colon cancer-related deaths increased by 5.8% annually between 2009 and 2015 and decreased by 3.3% annually between 2015 and 2019 (p < 0.05), pancreatic cancer-related deaths increased annually by 5.6% in 2009–2013 (p < 0.05). Among women; lung cancer-related deaths increased by 2.5% annually between 2009 and 2016 (p < 0.05), stomach cancer-related deaths increased annually by 2.3% between 2009 and 2014 and decreased annually by 4.5% between 2014 and 2019 (p < 0.05), colon cancer-related deaths increased by 2.5% annually between 2009 and 2017 (p < 0.05), pancreatic cancer-related deaths increased by 7.4% annually between 2009 and 2013 (p < 0.05) and breast cancer-related deaths increased by 2.2% annually between 2009 and 2019 (p < 0.05). Conclusion: Mortality data in Turkey are collected only by TURKSTAT, which raises concern regarding the incompletion of the data. While this might lead to underestimation, the trend shows that there has been a decrease in total cancer-related deaths in Turkey. Pancreatic cancer, on the other hand, gains a higher proportion in cancer-related deaths in Turkey as in the world. Increasing deaths from lung and breast cancer in women remind of the importance of tobacco control interventions and cancer screening programs.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; Social Sciences and Humanities; Sociology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Klinik Tıp; Moleküler Biyoloji ve Genetik; Sosyal Bilimler Genel; ONKOLOJİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Life Sciences (LIFE); Social Sciences (SOC); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; SOCIAL SCIENCES, GENERAL; ONCOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Epidemiyoloji; Kanser Araştırmaları; Epidemiology; Cancer Research; Cancer; Malignant neoplasms; Mortality; Joinpoint regression analysis; Trend; Turkey; The authors declared that they covered the financial expenses of the study; LUNG-CANCER; MORTALITY; REGISTRIES